PENGARUH STRUKTUR OWNERSHIP DAN TAX PLANNING TERHADAP FIRM VALUE DENGAN MANAJEMEN LABA SEBAGAI VARIABEL PEMODERASI - Sihotang, Wimbildon; Sitorus, Riris Rotua (Universitas 17 Agustus 1945 Jakarta, 2018)
This study was conducted to examine the effect of institutional ownership, managerial ownership, and tax planning on firm value and examination of influence of moderation of earnings management on the influence of institutional ownership, managerial ownership, and tax planning on firm value. This research was conducted at the company of propety and real estate between 2013-2017 with sample selection using purposive sampling method and produce 31 companies to be studied. Institutional ownership and managerial ownership are measured by percentage of ownership, effective tax rate proxied by ETR, earnings management is proxied by discretionary accrual, and firm value is proxied by price to book value. The result of this research is instiusional ownership has significant influence to firm value, managerial ownership and tax planning does not influence firm value, earnings management moderation can strengthen influence of institutional ownership to firm value, earnings management moderation can not strengthen managerial ownership and tax planning influence to firm value.Keywords : Firm Value, Institusional Ownership, Managerial Ownership, Tax Planning, Earnings Management.